Strength-Training Protocols to Improve Deficits in Participants With Chronic Ankle Instability: A Randomized Controlled Trial - Hall, Emily A. (J Athl Train, 2015)
CONTEXT: Although lateral ankle sprains are common in athletes and can lead to chronic ankle instability (CAI), strength-training rehabilitation protocols may improve the deficits often associated with CAI. OBJECTIVE: To determine whether strength-training protocols affect strength, dynamic balance, functional performance, and perceived instability in individuals with CAI. DESIGN: Randomized controlled trial. SETTING: Athletic training research laboratory. PATIENTS OR OTHER PARTICIPANTS: A total of 39 individuals with CAI (17 men [44%], 22 women [56%]) participated in this study. Chronic ankle instability was determined by the Identification of Functional Ankle Instability Questionnaire, and participants were randomly assigned to a resistance-band–protocol group (n = 13 [33%] age = 19.7 ± 2.2 years, height = 172.9 ± 12.8 cm, weight = 69.1 ± 13.5 kg), a proprioceptive neuromuscular facilitation strength-protocol group (n = 13 [33%], age = 18.9 ± 1.3 years, height = 172.5 ± 5.9 cm, weight = 72.7 ± 14.6 kg), or a control group (n = 13 [33%], age = 20.5 ± 2.1 years, height = 175.2 ± 8.1 cm, weight = 70.2 ± 11.1 kg). INTERVENTION(S): Both rehabilitation groups completed their protocols 3 times/wk for 6 weeks. The control group did not attend rehabilitation sessions. MAIN OUTCOME MEASURE(S): Before the interventions, participants were pretested by completing the figure-8 hop test for time, the triple-crossover hop test for distance, isometric strength tests (dorsiflexion, plantar flexion, inversion, and eversion), the Y-Balance test, and the visual analog scale for perceived ankle instability. Participants were again tested 6 weeks later. We conducted 2 separate, multivariate, repeated-measures analyses of variance, followed by univariate analyses on any significant findings. RESULTS: The resistance-band protocol group improved in strength (dorsiflexion, inversion, and eversion) and on the visual analog scale (P < .05); the proprioceptive neuromuscular facilitation group improved in strength (inversion and eversion) and on the visual analog scale (P < .05) as well. No improvements were seen in the triple-crossover hop or the Y-Balance tests for either intervention group or in the control group for any dependent variable (P > .05). CONCLUSIONS: Although the resistance-band protocol is common in rehabilitation, the proprioceptive neuromuscular facilitation strength protocol is also an effective treatment to improve strength in individuals with CAI. Both protocols showed clinical benefits in strength and perceived instability. To improve functional outcomes, clinicians should consider using additional multiplanar and multijoint exercises.